PENERAPAN DIVERSI TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DALAM KASUS TINDAK PIDANA PENCURIAN (STUDI KASUS PENGADILAN NEGERI SIBOLGA NOMOR 2/PID/SUS-ANAK/2016/PN.SBG) - Dian Adriawan Dg Tawang; Mikenda Adiputra Tumanggor (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
The constitution Number 11 of 2012 concerning the criminal system of children article 1 pharagraph 7 explain that diversion is the transfer of settlement of child cases and criminal justices proccess to proccess other than criminal. The intended application of diversion effort to children in conflict with the law in criminal case against No.2/PID/Su/2017. The method carried out the another after conducting research is a normative method with interviews. Diversion is a case settlement in a crimw, cartied out by a child and resolved outside the court proccess. The constitution not only provides facilities but required to be completed outside the constitution especially before the trial proccess. This matter in clause 5 pharagraph 3 is strengthened in article 7 pharagraph 1. It seems that the problems of the research have not fully carried out special attention from low enfources in realizing what was written in the constitution . In this cases, it is expected for low enforces to give more attention and considering the best interests of children in handling child criminal cases.